2015
DOI: 10.1021/acs.jmedchem.5b00825
|View full text |Cite
|
Sign up to set email alerts
|

A Journey around the Medicinal Chemistry of Hepatitis C Virus Inhibitors Targeting NS4B: From Target to Preclinical Drug Candidates

Abstract: Hepatitis C virus (HCV) infection is a global health burden with an estimated 130-170 million chronically infected individuals and is the cause of serious liver diseases such as cirrhosis and hepatocellular carcinoma. HCV NS4B protein represents a validated target for the identification of new drugs to be added to the combination regimen recently approved. During the last years, NS4B has thus been the object of impressive medicinal chemistry efforts, which led to the identification of promising preclinical can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 103 publications
0
22
0
Order By: Relevance
“…Interestingly, several structurally distinct compounds have been identified that inhibit DENV or YFV replication through targeting NS4B (40,(63)(64)(65)(66)(67). In addition, multiple inhibitors of the NS4B protein of hepatitis C virus, a distantly related member of the Flaviviridae family, are currently under preclinical and clinical development for treatment of hepatitis C infection (68). Intriguingly, as summarized in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several structurally distinct compounds have been identified that inhibit DENV or YFV replication through targeting NS4B (40,(63)(64)(65)(66)(67). In addition, multiple inhibitors of the NS4B protein of hepatitis C virus, a distantly related member of the Flaviviridae family, are currently under preclinical and clinical development for treatment of hepatitis C infection (68). Intriguingly, as summarized in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 127 RAVs in NS3, NS4B, NS5A, and NS5B were included in the study (Supplementary Table S4 ). RAVs were obtained by merging six recently compiled lists of naturally occurring variants associated with DAA resistance ( Rai and Deval, 2011 ; Bartenschlager et al, 2013 ; Lontok et al, 2015 ; Cannalire et al, 2016 ; Chen et al, 2016 ; Patino-Galindo et al, 2016 ). Specifically, a list of positions where RAVs have been reported was compiled, irrespective of the viral genotype carrying the RAV.…”
Section: Methodsmentioning
confidence: 99%
“…However, DAAs have limited pan-genotypic activity and tend to select for resistance-associated amino acid variants (RAVs) ( Lontok et al, 2015 ). Most RAVs naturally occur in treatment-naive patients and in some instances RAV prevalence differs among genotypes or subtypes ( Rai and Deval, 2011 ; Bartenschlager et al, 2013 ; Lontok et al, 2015 ; Cannalire et al, 2016 ; Chen et al, 2016 ; Patino-Galindo et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Quinoline derivatives represent an important class of heterocyclic compounds utilized as pharmaceuticals (Chu et al, 2019). They possess various biological properties such as antibacterial (Panda et al, 2015), anticancer (Tang et al, 2018), antitubercular (Xu et al, 2017), antiviral (Sekgota et al, 2017), anti-HCV (Cannalire et al, 2016), antimalarial (Hu et al, 2017), anti-Alzheimer's (Bolognesi et al, 2007), antileishmanial (Palit et al, 2009) and anti-inflammatory (Pinz et al, 2016) activities.…”
Section: Chemical Contextmentioning
confidence: 99%